2015
DOI: 10.1007/s12070-015-0889-5
|View full text |Cite
|
Sign up to set email alerts
|

Audiological and Electrophysiological Changes in Patients with Vitiligo

Abstract: The study was conducted to evaluate the audiological and electrophysiological findings in patients with Vitiligo and to compare the findings with otologically and audiologically normal controls. Study group included 50 subjects (25 Males, 25 Females) with Vitiligo (Mean age-27.4 years) and control group contained 40 age-matched normal hearing subjects. Pure tone audiometry (PTA) with extended high frequency audiometry, Otoacoustic emissions (OAEs), Tympanometry, Auditory brainstem responses (ABR) and Middle la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…(2016) . On the other hand, the result of the study disagree with Arya et al. (2015) who found statistical difference in average amplitude of TOAEs in two groups (localized and generalized) in left ear at 2, 3 & 4 KHz.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…(2016) . On the other hand, the result of the study disagree with Arya et al. (2015) who found statistical difference in average amplitude of TOAEs in two groups (localized and generalized) in left ear at 2, 3 & 4 KHz.…”
Section: Discussioncontrasting
confidence: 99%
“…This result strengthens the hypothesis that vitiligo is a significant factor for altered cochlear function, and that melanin as assumed could have an important role in cell metabolism, facilitating substance exchange and maintain endolymph, perilymph and ionic balance. Similar results obtained by Arya et al. (2015) who studied the audiological and electrophysiological changes in patients with vitiligo and to compare the finding with otologically and audiologically normal controls.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In another study, a significant prevalence of hearing impairment has been reported in patients with vitiligo ( 16 ). In the study of Arya et al, It was found that the cochlea function reduced in patients with vitiligo, result in hearing impairment, so, they recommended a complete auditory monitoring for these patients ( 22 ).…”
Section: Discussionmentioning
confidence: 99%